Effects of Lower Dietary Calcium and Phosphorus on Growth Performance and Bone Mineralizatıon of Broilers - Ceylan, N; Koca, S; Yavaş, İ; Çenesiz, AA (Journal of the Hellenic Veterinary Medical Society, 2023)
This experiment was carried out to investigate the effects of reduced dietary calcium (Ca) and non-phytate-phosphorus (NPP) levels at 2:1 constant ratio on performance, carcase parameters and bone mineralization of Ross-308 broilers. A total of 11400 one-day-old chicks were randomly allocated to five dietary treatments with twelve replicates and were fed starter diets including either recommended (control treatment, T1) or a 6.25% lower level of both Ca and NPP according to breeder’s recommendations during starter period (SP). After SP, control treatment (T1) continued to be provided through diets containing 0.87 and 0.78 % Ca for grower (GP) and finisher periods (FP), respectively, while 6.25 % reduced group was divided into 4 dietary treatments regarding extent of decrease in Ca and NPP levels and provided by diets containing 0.79;0.65 (T2), 0.79;0.60 (T3), 0.75;0.65 (T4), and 0.75;0.60 (T5) % Ca for GP and FP, respectively. After SP, moderate and even substantial reduction of Ca and NPP significantly decreased feed intake (FI) (quadratic, P<0.05), but obtained similar body weight gain (BWG) and FCR compared to the control (P>0.05). On the other hand, reduced dietary Ca through T1 to T5 significantly decreased the total Ca and NPP intake of broilers (linear and quadratic, P<0.01), and accompanied to significant linear and quadratic relationship between Ca intake and FCR and BWG respectively. It can be concluded that reducing Ca level down to 0.75 and 0.60 % in grower and finisher phase, respectively are possible without compromising the growth performance and bone mineralization of modern broilers.